2019
DOI: 10.21608/ejabf.2019.57913
|View full text |Cite
|
Sign up to set email alerts
|

Use of green alga Ulva lactuca (L.) as an indicator to heavy metal pollution at intertidal waters in Suez Gulf, Aqaba Gulf and Suez Canal, Egypt

Abstract: Metal pollution in the marine coastal line environment is an important topical issue in the context of ecological disturbance. The concentration of nine trace elements: Cu, Co, Ni, Cr, Mn, Zn, Cd, Pb, and Fe was determined in water, sediments and the green alga Ulva lactuca (L.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…45 Mourad and El-Azim's research (2019) on macroalgae showed a positive correlation between Cu and Cd, Cu with Pb, Fe with Pb, Zn with Pb, Fe with Cu, and Zn with Cu. 46 The concentrations of metals in C. racemosa correlate with each other, which indicates that an increase in the levels of one metal affects others.…”
Section: Resultsmentioning
confidence: 97%
“…45 Mourad and El-Azim's research (2019) on macroalgae showed a positive correlation between Cu and Cd, Cu with Pb, Fe with Pb, Zn with Pb, Fe with Cu, and Zn with Cu. 46 The concentrations of metals in C. racemosa correlate with each other, which indicates that an increase in the levels of one metal affects others.…”
Section: Resultsmentioning
confidence: 97%
“…absorb and accumulate heavy metals and various pollutants in the intertidal zone. Therefore, pollution monitoring and ecosystem stability evaluations are conducted by examining the changes in biomass and pollutant concentrations accumulated in fronds [40][41][42][43]. Ulva spp.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is a good idea to exploit such massive biomass to remove toxic substances from the environment. U. lactuca is well known for its efficiency in the defense process through its release of an efficient amount of polyunsaturated aldehyde [15] as well as its ability as an adsorbent of heavy metals [16][17][18] and toxic substances like dyes [19] and phenols [14]. As a cationic and thiazine dye, MB is widely applied in several fields, e.g., industry, biology, chemistry, and medicine, which is the reason behind its existence in large amounts in water bodies, contributing to the depletion of the photosynthesis rate and having a direct effect on aquatic organisms, resulting in damage to the water environment [20,21].…”
Section: Introductionmentioning
confidence: 99%